The Effect of Augmented Reality Technology on Science Learning in Elementary School - Rosmaria Rosmaria; Titin mairisiska (PT. Anagata Sembagi Education, 2024)
This research aims to explore the influence of Augmented Reality (AR) technology in science learning in elementary schools. AR is proven to be effective in helping students understand science concepts that are difficult to explain through conventional methods, such as the solar system and photosynthesis, by providing interactive three-dimensional visualizations. It can also increase student motivation and engagement, making learning more interesting and fun. In addition, AR supports the development of critical thinking and problem-solving skills through simulated virtual experiments. Despite its great potential, AR implementation faces challenges related to the cost of devices, infrastructure and teacher training. To overcome this, support from various parties is needed, including the government, private sector, and educational institutions. This research uses a descriptive qualitative method with interviews, group discussions, observations, and document analysis in three elementary schools. The results are expected to provide insights into the benefits of AR in improving concept understanding, critical thinking skills, as well as identification of challenges and optimal strategies in its implementation. Hopefully, the findings can provide recommendations for educators and policy makers in effectively integrating AR in the science learning curriculum in elementary schools